2010
DOI: 10.1038/eye.2010.135
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma surgery: trainee outcomes and implications for future training: southeast Scotland

Abstract: Trainee trabeculectomy cases showed significantly higher rates of early complications, return to theatres, and bleb interventions compared with consultant cases. Satisfactory IOP control was achieved in both groups at postoperative year 1. Trainee cases require careful preoperative selection, avoiding complicated glaucomas including pseudoexfoliation and low tension, and those that require mitomycin. The majority of Scottish consultants wish to retain glaucoma surgery within the remit of generic training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 20 publications
5
24
0
Order By: Relevance
“…Over the 2 year period the trainee group had a statistically significant higher complication rate, with bleb leaks and hypotony being the most frequent complications. This chimes with the findings of Welch et al who have shown previously that trainee trabeculectomies have higher return to theatre rates associated with bleb leaks [7]. Interestingly in their subgroup analysis of the MMC trabeculectomies they also found trainee cases had significantly higher return to theatre rates.…”
Section: Discussionsupporting
confidence: 88%
“…Over the 2 year period the trainee group had a statistically significant higher complication rate, with bleb leaks and hypotony being the most frequent complications. This chimes with the findings of Welch et al who have shown previously that trainee trabeculectomies have higher return to theatre rates associated with bleb leaks [7]. Interestingly in their subgroup analysis of the MMC trabeculectomies they also found trainee cases had significantly higher return to theatre rates.…”
Section: Discussionsupporting
confidence: 88%
“…Resident performed glaucoma surgery has been addressed by several studies and found to be similar in IOP lowering and overall success rates long term when compared with faculty or attending surgery. [11][12][13][14] Most of these studies compared and found similar complication rates as well, although 1 study did report higher complication rates in trainee performed cases. 11 Our results suggest that trainee performed surgery has similar success and complication rates to the published literature.…”
Section: Discussionmentioning
confidence: 89%
“…[11][12][13][14] Most of these studies compared and found similar complication rates as well, although 1 study did report higher complication rates in trainee performed cases. 11 Our results suggest that trainee performed surgery has similar success and complication rates to the published literature. 21 This makes it impossible to choose a definition of success that makes comparison across all studies valid.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations